2022
DOI: 10.1183/13993003.01117-2022
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary shunt and alveolar dead space in a cohort of patients with acute COVID-19 pneumonitis and early recovery

Abstract: BackgroundPathological evidence suggests that COVID-19 pulmonary infection involves both alveolar damage (causing shunt) and diffuse micro-vascular thrombus formation (causing alveolar dead space). We propose that measuring respiratory gas exchange enables detection and quantification of these abnormalities. We aimed to measure shunt and alveolar deadspace in moderate COVID-19 during acute illness and recovery.MethodsWe studied 30 patients (22 males, age: 49.9±13.5 years) 3–15 days from symptom onset and again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In a recent study (2), we could demonstrate the involvement of the secondary pulmonary lobules in the fatal trajectory of COVID-19 using ultra-high resolution synchrotron radiation based hierarchical phase-contrast tomography (HiP-CT) (3) (Figure a-c). We observed a distinct, mosaic-like consolidation of individual secondary pulmonary lobules based on microvascular occlusion and secondary lobular microischemia, reflecting the increased alveolar dead space described by Harbut et al (1). Moreover, this septal microischemia was accompanied by a periseptal thickening (F) and pronounced dilatation and expansion of the bronchial circulation plexus by opening of intrapulmonary bronchopulmonary shunts and "Sperrarterien" (specialized blockade arteries of the bronchial circulation) (4,5) and an excessive blood vessel neoformation by intussusceptive angiogenesis, especially in the interlobular septae (2,6,7) (Figure d-g).…”
supporting
confidence: 71%
“…In a recent study (2), we could demonstrate the involvement of the secondary pulmonary lobules in the fatal trajectory of COVID-19 using ultra-high resolution synchrotron radiation based hierarchical phase-contrast tomography (HiP-CT) (3) (Figure a-c). We observed a distinct, mosaic-like consolidation of individual secondary pulmonary lobules based on microvascular occlusion and secondary lobular microischemia, reflecting the increased alveolar dead space described by Harbut et al (1). Moreover, this septal microischemia was accompanied by a periseptal thickening (F) and pronounced dilatation and expansion of the bronchial circulation plexus by opening of intrapulmonary bronchopulmonary shunts and "Sperrarterien" (specialized blockade arteries of the bronchial circulation) (4,5) and an excessive blood vessel neoformation by intussusceptive angiogenesis, especially in the interlobular septae (2,6,7) (Figure d-g).…”
supporting
confidence: 71%
“…The study by H arbut et al [ 1 ] reported in this issue of the European Respiratory Journal analyses gas exchange in patients with acute coronavirus disease 2019 (COVID-19) lung disease; arterial oxygen and carbon dioxide tension ( P O 2 and P CO 2 ) and the mean (or mixed) value for alveolar (A̅) P O 2 and P CO 2 (not an “ideal” [ 2 ] but the actual value) were measured, when patients (and healthy controls) were breathing air. From the mean alveolar to arterial P O 2 and arterial to mean alveolar P CO 2 gradients (A̅a P O 2 and aA̅ P CO 2 ), the authors computed intrapulmonary shunt and alveolar dead space using the classical three compartment model of R iley and C ournand [ 2 ] (but, with important differences: see later).…”
Section: Intrapulmonary Shunt and Alveolar Dead Space In Covid–19 Pne...mentioning
confidence: 99%
“…From the mean alveolar to arterial P O 2 and arterial to mean alveolar P CO 2 gradients (A̅a P O 2 and aA̅ P CO 2 ), the authors computed intrapulmonary shunt and alveolar dead space using the classical three compartment model of R iley and C ournand [ 2 ] (but, with important differences: see later). H arbut et al [ 1 ] argued that intrapulmonary shunt should be a marker for alveolar consolidation, as in lobar pneumonia, but at a more microscopic level; alveolar dead space, on the other hand, should be a surrogate for pulmonary microvascular obstruction and thrombosis, e.g. following severe endothelial injury.…”
Section: Intrapulmonary Shunt and Alveolar Dead Space In Covid–19 Pne...mentioning
confidence: 99%
See 2 more Smart Citations